The Influence of Leadership Style, Communication, and Motivation on Employee Performance at Pt. Fengtay Indonesia Enterprise - Rima Nurul Afifah; Gurawan Dayona Ismail; Yoyo Sudaryo; Dayan Hakim Natigor Sipahutar; Dadan Abdul Aziz Mubarok (Syntax Idea)
This research was conducted for problems that occurred at PT. Fengtay Indonesia Ent. namely low employee performance, this is characterized by a decline in employee performance which is assessed through IPT (Individual Performance Targets) and UPT (Unit Performance Targets) never reaching the IPT and UPT targets. Then the level of employee discipline decreases. These problems must of course be addressed immediately, because employees are one of the factors that can determine the success of a company. The aspects examined in this research are leadership style, work communication, and motivation. This research uses quantitative methods with descriptive and verification approaches. In this research, quantitative methods with descriptive and verification approaches are used to test whether there is an influence of leadership style, communication and motivation on the performance of PT employees. Fengtay Indonesia Enterprise. The results of this research show that with good leadership style, work communication, motivation, employee performance will increase and achieve targets.